PENGARUH PENGGUNAAN MODEL PEMBELAJARAN LEARN ON DELIVERY (LEADER) TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI KELAS X DI SMA MUHAMMADIYAH BOARDING SCHOOL TARAKAN - Bhekti Ramadani; Fitri Wijarini; Aidil Adhani (Biopedagogia, 2022)
Abstract : This research aimed to figure out the influence of Learn On Delivery (Leader) learning model on biology learning outcomes of Grade X students at SMA Muhammadiyah Boarding School Tarakan. The research employing Quasi Experimental method with a Non Equivalent Control Group Design was conducted in March for two meetings with the samples of X mia 1 (experimental class) and X mia 2 (control class). The data were collected using observations, formative tests in the form of 30 multiple choice questions, and documentation. The normality test shows tha significance value was 0.05, meaning that the samples were normally distributed. The homogeneity tests shows the value of 0.185 and 0.140 (sig 0.05), meaning that the data is homogeneous. The research results based on the Analysis of Covariance (anacova) show that Learning On Delivery (Leader) learning model which influenced learning outcomes was feasible seen from the sig value of 0.000 ( 0.05) with F value of 46.981 (corrected model) in the table (tests of between-subjects effects) with the significant value of 0.000 (p0.05), meaning that H0 was rejected. The role of “covariates” is determining the class average differences could be seen from pretest scores in which the significance value was 0.166 ( 0.05). Thus, in this anacova model, the role of covariate in pretest was not significant. Keywords : learning model, Learn On Delivery (Leader), Learning outcomes